2002
DOI: 10.1007/s00213-002-1175-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on mood and performance: a study of realistic consumption

Abstract: These results suggest that previous findings from studies using a large single dose may be applicable to normal patterns of caffeine consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 22 publications
6
74
1
2
Order By: Relevance
“…This strengthens the assumption that the observed effect of caffeine within the frontal cortex was of a neuromodulatory sort. In contrast to several other psychopharmacological studies [7,8,10,76], no significant caffeine-related behavioral effects were observed. The researchers argued that this difference could be due to the rather low dosage of caffeine used in this study, which was chosen to avoid physiological side effects noticeable to the volunteers, as well as to reflect caffeine intake of common drinking habits.…”
Section: Imaging the Effects Of Caffeine On Cognitioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This strengthens the assumption that the observed effect of caffeine within the frontal cortex was of a neuromodulatory sort. In contrast to several other psychopharmacological studies [7,8,10,76], no significant caffeine-related behavioral effects were observed. The researchers argued that this difference could be due to the rather low dosage of caffeine used in this study, which was chosen to avoid physiological side effects noticeable to the volunteers, as well as to reflect caffeine intake of common drinking habits.…”
Section: Imaging the Effects Of Caffeine On Cognitioncontrasting
confidence: 96%
“…Nevertheless, caffeine has been found to enhance task performance through increase of a) cortical activation, b) the rate at which information about a stimulus accumulates, c) selectivity to further processing of the primary attribute, and d) speed of motor processes via central or peripheral mechanisms [6]. It is not clear yet whether the observed beneficial effects on learning, memory, and performance derive from a direct enhancement of specific cognitive functions or can be attributed to increasing of arousal and overcoming fatigue [7][8][9][10].…”
mentioning
confidence: 99%
“…In addition, psychostimulants, such as caffeine, are usually thought of as nootropics [e.g. 15,26,49]. This folklore is exemplified by the advertisement campaign of the original Coca-Cola that contained cocaine, declaring it "the brain tonic and intellectual sodafountain beverage" [51].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the benefits of daytime caffeine consumption in nonexperimentally sleep-deprived individuals (Loke et al 1985;Lieberman et al 1987;Zwyghuizen-Doorenbos et al 1990;Nehlig et al 1992;Dimpfel et al 1993;Spriet 1995;Lorist et al 1996;Kaplan et al 1997;Brice et al 2002;Lorist et al 2003;Cysneiros et al 2007). The performance tasks used in these studies measure reaction time and motor speed, speed of information processing, vigilance and attention, immediate and delayed verbal memory, as well as mood and alertness (for review see (Nehlig et al 1992;Lorist et al 2003).…”
Section: Introductionmentioning
confidence: 99%